Handbook of meat, poultry and seafood quality - Nollet, Leo M. L., 1948- (Wiley, 2012)
A great need exists for valuable information on factors affecting the quality of animal related products. The second edition of Handbook of Meat, Poultry and Seafood Quality, focuses exclusively on quality aspects of products of animal origin, in depth discussions and recent developments in beef, pork, poultry, and seafood quality, updated sensory evaluation of different meat products, revised microbiological aspects of different meat products. Also, included are new chapters on packaging, new chapters and discussion of fresh and frozen products, new aspects of shelf life and recent de.